Some Issues to Increase the Operational Efficiency of Multiphase Flow of Subsea Pipelines - Ismayilov, G.G.; Shahlarli, M.E.; Ismayilov, Sh.Z. (Herald of Azerbaijan Engineering Academy, 2022)
The paper examines the problem in risers and in the case of multiphase flow due to the relief of the seabed, and shows the desirable and undesirable conditions in the curves rising from the seabed to the platform, ie in the elbow sections. The undesirable conditions that occur in the part of the pipe that rises to the platform, ie in the elbow sections of the vertical pipe, are shown mathematically. Due to the relief of the seabed, the accumulation of mechanical solids in the depressions of subsea pipelines between platforms and from the platform to the shoreline considering that it leads to the perforation of subsea pipelines and environmental pollution, in the latter part a technological scheme is proposed to prevent such cases. The technological scheme is simulated according to the results of laboratory analysis by Aspen HYSYS program and graphical dependences of various thermodynamic parameters were given.